Numerical simulation of three-dimensional supersonic flow around an aerodynamic bump - A. Mohammed, Hussein (2013)
This s tudy is used to compute the primitive variables of moderate supersonic flow based on finite differen ce computational fluid dynamic methods. The problem considered deals with a three - dimensional external, inviscid ,compressible supersonic flow over a thre e - dimensional arc circular bump. In this work, Euler equation was solved using time - marching Mac Cormack’s explicit technique. The flow conditions are taken at sea level and Mach number at 1.97 . To deal with complex shape of arc circular bump the so - called “body fitted coordinate system” were considered and the algebraic methods were used to generate grids over an arc circular bump. The results showed a good agreement with other published results.